Viral RNA and Infectious Influenza Virus on Mobile Phones of Patients With Influenza in Hong Kong and the United States. (17th September 2021) - Xiao, Jingyi; Bueno de Mesquita, P Jacob; Leung, Nancy H L; Adenaiye, Oluwasanmi; Tai, Sheldon; Frieman, Matthew B; Hong, Filbert; Chu, Daniel K W; Ip, Dennis K M; Cowling, Benjamin J; Milton, Donald K
Abstract: Mobile phones are among the most highly touched personal objects. As part of a broader study on the contribution of fomites to influenza transmission, between 2017 and 2019, we swabbed mobile phones from 138 patients with influenza in 2 locations. Influenza viral RNA detection rates were 23% (23 of 99 phones) and 36% (14 of 39) in Hong Kong and Maryland, respectively. In Hong Kong, infectious influenza virus was recovered from 3 of 23 mobile phones which had influenza viral RNA detected. Mobile phone influenza contamination was positively associated with upper respiratory tract viral load and negatively associated with age. Cleaning personal objects of patients with influenza should be recommended, and individuals should avoid sharing objects with these patients. Abstract : We swabbed mobile phones from 138 patients with influenza in 2 locations. Influenza viral RNA detection rates were 23% (23 of 99 phones) and 36% (14 of 39) in Hong Kong and Maryland, respectively. In Hong Kong, infectious virus was recovered from 3 mobile phones.